1987
DOI: 10.1111/j.1432-1033.1987.tb11464.x
|View full text |Cite
|
Sign up to set email alerts
|

Activation mechanism of monkey and porcine pepsinogens A. One-step and stepwise activation pathways and their relation to intramolecular and intermolecular reactions

Abstract: The activation of Sepharose-bound monkey pepsinogen A under acidic conditions proceeded by cleavage of the L e~~~-I l e~' bond, indicating the occurrence of the intramolecular one-step activation, although the rate of cleavage was very slow. On the other hand the activation of monkey pepsinogen A in solution was highly dependent on pepsinogen concentration and the addition of exogenous pepsin A accelerated the rate of activation, indicating the predominance of intermolecular reaction. The cleavage site, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1991
1991
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 35 publications
1
18
0
Order By: Relevance
“…(42) as a function of the initial pepsinogen concentration at different reaction times, using the values obtained for K 2 , k 3 and K 4 . The results obtained are in agreement with those of Kageyama and Takahashi (1987), who indicated that the intramolecular reaction is especially important in the ini-tial phase of the activation process to generate the active enzyme, and that the intermolecular reaction plays a significant role in acceleration and completion of the activation. However, as Z 0 is increased and at higher reaction times, r values are less than 1, indicating that the bimolecular reaction becomes more important under these conditions.…”
Section: Relative Contribution Of the Intra-and Intermolecular Routessupporting
confidence: 91%
See 1 more Smart Citation
“…(42) as a function of the initial pepsinogen concentration at different reaction times, using the values obtained for K 2 , k 3 and K 4 . The results obtained are in agreement with those of Kageyama and Takahashi (1987), who indicated that the intramolecular reaction is especially important in the ini-tial phase of the activation process to generate the active enzyme, and that the intermolecular reaction plays a significant role in acceleration and completion of the activation. However, as Z 0 is increased and at higher reaction times, r values are less than 1, indicating that the bimolecular reaction becomes more important under these conditions.…”
Section: Relative Contribution Of the Intra-and Intermolecular Routessupporting
confidence: 91%
“…Physiological examples of these processes are the activation of prekallikrein to kallikrein (Magklara et al, 2003;Shariat-Madar et al, 2004), the conversion of trypsinogen to trypsin (Manjabacas et al, 1995;Liu and Wang, 2004) and the activation of pepsinogen to pepsin (Al-Janabi et al, 1972;Kageyama and Takahashi, 1987;Kageyama, 1988;Kageyama et al, 1989;Nielsen and Foltmann, 1993;Richter et al, 1998). Physiological examples of these processes are the activation of prekallikrein to kallikrein (Magklara et al, 2003;Shariat-Madar et al, 2004), the conversion of trypsinogen to trypsin (Manjabacas et al, 1995;Liu and Wang, 2004) and the activation of pepsinogen to pepsin (Al-Janabi et al, 1972;Kageyama and Takahashi, 1987;Kageyama, 1988;Kageyama et al, 1989;Nielsen and Foltmann, 1993;Richter et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of immobilized pepsinogen is thought to be suitable to clarify intramolecular reactions. With Sepharose-bound porcine pepsinogen A, cleavage has been shown to generate pseudopepsin A [75,76], while pepsin A is generated with immobilized monkey pepsinogen A [83]. The involvement of intramolecular reactions might also be estimated in terms of excess substrate since intermolecular reactions between pepsinogens or between pepsinogen and pepsin may be hindered under this condition [84 -86].…”
Section: Zymogen Activationmentioning
confidence: 99%
“…Apart from two different activation pathways, two different cleavage reactions are possible for activation: in- Figure 4. The primary cleavage sites upon activation of various pepsinogens are summarized based on the results of pepsinogens A from human [80,87], monkey [12,73,83], pig [74,76], cattle [142], bear [69], house musk shrew [29], rabbit [13], and chicken [81]; cattle pepsinogen B [38]; progastricsins from human [77], monkey [12,83], pig [143], house musk shrew [29], and frog [22]; cattle prochymosin [78]; and tuna pepsinogens [144]. The residues in the activation segment are numbered according to the porcine pepsinogen A sequence and characterized by the suffix p. Residues in filled boxes are conserved in these sequences.…”
Section: Zymogen Activationmentioning
confidence: 99%
“…(Tokyo, Japan) ; oligo(dT)-cellulose, the cDNAsynthesis kit, the pUC-cloning kit, and cloning vectors M23mp18 and M13mp19 (replicable forms) were obtained from Boehringer Mannheim GmbH (Mannheim, Federal Republic of Germany) cloning vector llgtlO and the DNA in vitro packaging kit (Gigapack Gold) were from Stratagene Cloning System (SCS) (La Jolla, CA, USA); the SequenaseTM DNA Table S2. Scmzniury of the activution of pepsinogen isoqmogens Activation was carried out at pH 2.0 and at pH 3.0. at 14"C, by the procedure described previously [40]. t s O (Pg) and tS0 (p) represent times needed for the disappearance of half of the initial amount of pepsinogen, and for the increase in the level of pepsin up to half of the equivalent amount of the initial pepsinogen, respectively.…”
Section: Chemicalsmentioning
confidence: 99%